Mathematical Literacy Ability in Probing Prompting Learning Based on Self-Confidence Assited by Schoology - Danieryanto, Erlia; wardono, Wardono; Rosyida, Isnaini (Educational Management, 2021)
Mathematical literacy ability and self-confidence are important in learning mathematics for students' needs. An innovative learning model is needed that can boost up their mathematical literacy ability and self-confidence, named Probing Prompting assisted by Schoology. The research aims (1) to determined the quality of Probing Prompting assisted by Schoology (2) described students' mathematical literacy abilities based on self-confidence after being subjected to probing prompting learning. The study used a qualitative method. The student population was students of class VII SMP N 33 Semarang with two sample classes. The results showed that (1) Probing Prompting assisted by Schoology have certain quality for students’ mathematical literacy ability (2) students with high self-confidence have mathematical literacy ability in all indicators, students with medium self-confidence almost have all indicators of mathematical literacy ability, students with low self-confidence did not yet have complete the mathematical literacy ability for all indicators.